Cultural landscapes. Artificial between resilience and natural selection - Marina Fumo (Agathón)
Over fourteen thousand and up to twelve thousand years ago, due to a serious food supply crisis, homo sapiens implemented a new model of survival based on agriculture, starting to sow, man became more sedentary. Nowadays, we rely on a new adaptation process to bring us closer to farm and craft activities, reviving small scale settlement systems. Knowing the peculiar features of a natural or urban artificial landscape and identifying in it with a feeling of belonging, as a place bearing culture and traditions, has always linked the human beings to their territory, to a geographical context. In the current global environmental crisis, the rural landscape is once again considered an asset for man, especially for its cultural and spiritual values, as a fundamental scenario to build individual and collective life. Therefore, for every human community, the whole landscape becomes a place where to reside, live, build, produce, sell, pass on, it participates in the whole cycle.